2016
DOI: 10.1186/s12890-016-0272-7
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study of innate immunity pathway gene polymorphisms in Puerto Ricans reveals association of toll-like receptor 2 +596 variant with asthma

Abstract: BackgroundFor many years, African Dust Storms (ADE) has been thought to be associated with high prevalence of asthma in Puerto Rico (PR). Endotoxins (ENX) have been associated with ADE particulate matter (PM) and are known to promote pro-inflammatory responses in lung cells of susceptible individuals through the Toll-like receptor (TLR2/4) signaling pathways. Genetic variants are plausible contributors to such susceptibility. Therefore, we have evaluated a series of nine single nucleotide polymorphisms (SNPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Our results are consistent with studies in populations from Denmark, 30 Tunisia, 31 Egypt, 45 Korea, 46 and Japan 47 that did not find an effect of the TLR4/+896A/G polymorphism on the risk of asthma or atopy-related traits. In addition, similar results were obtained in both the Puerto Rican population 42 and a heterogeneous American cohort. 29 The lack of association between the TLR4/+896A/G polymorphism and asthma has also been confirmed by the latest metaanalysis.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our results are consistent with studies in populations from Denmark, 30 Tunisia, 31 Egypt, 45 Korea, 46 and Japan 47 that did not find an effect of the TLR4/+896A/G polymorphism on the risk of asthma or atopy-related traits. In addition, similar results were obtained in both the Puerto Rican population 42 and a heterogeneous American cohort. 29 The lack of association between the TLR4/+896A/G polymorphism and asthma has also been confirmed by the latest metaanalysis.…”
Section: Discussionsupporting
confidence: 79%
“…21,27,[38][39][40][41] A significant correlation between the CD14/-159C/T polymorphism and asthma was not observed in another recent study among the Puerto Rican population, the population that exhibits the highest asthma prevalence of any racial or ethnic group. 42 On the other hand, other authors have reported a correlation of the CD14-159/TT genotype with a lower risk of developing asthma 17,31,35,43 or have even reported the opposite results. 32,33,44 In the present study, the genotype and allele frequency of the TLR4/+896A/G polymorphism did not significantly differ between the allergic patients and the controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 ] Finally, 18 literatures were selected into the meta-analysis. [ 10 , 13 , 14 , 21 35 ] Figure 1 outlines our study selection process. The characteristics of studies included in the analysis were listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 12 ] During the past years, several studies about TLR gene polymorphisms and asthma have been conducted. [ 13 , 14 ] So, we conducted the update meta-analysis expecting to give a more determinately conclusion.…”
Section: Introductionmentioning
confidence: 99%